In vitro wound healing potential of flavonoid C-glycosides from oil palm (Elaeis guineensis Jacq.) leaves on 3T3 fibroblast cells - Che Zain, Mohamad Shazeli; Lee, Soo Yee; Sarian, Murni Nazira; Fakurazi, Sharida; Shaari, Khozirah (MDPI, 2020)
Oil palm (Elaeis guineensis Jacq.) leaves (OPL) are widely available at zero cost in Southeast Asia countries, especially in Malaysia and Indonesia due to large scale oil palm plantations. OPLs contain a large amount of flavonoids in particular flavonoid C-glycosides, which are known to possess useful biological properties including antioxidant and wound healing properties. The present study aimed at evaluating the wound healing efficacy of OPL in various solvent extracts and flavonoid enriched fractions and to determine the contribution of flavonoid C-glycosides (orientin, isoorientin, vitexin and isovitexin) using in-vitro scratch assay on 3T3 fibroblast cells. Solvent crude extracts with different polarity were screened and the most active extract was subjected to acid hydrolysis. The crude and acid hydrolysed extracts were further enriched using macroporous resins, XAD7HP. UHPLC-UV/PDA and LC-MS/MS analysis were applied for identification and confirmation of flavonoid C-glycosides. The wound healing properties comprised of cell viability, cell proliferation and cell migration were studied. Allantoin was used as a positive control to compare the efficacy among the tested samples. The results revealed all OPL crude extracts, flavonoid enriched fractions and flavonoid C-glycosides were non-toxic at concentrations below 25 µg/mL and showed better cell proliferation and migration activities at low concentrations than higher concentrations.. This study also demonstrated orientin, isoorientin, vitexin and isovitexin presented in OPL extracts and flavonoid enriched fractions stimulated proliferation and migration of 3T3 fibroblast cells. Hence, these findings may pose potential therapeutic bioactive agents for wound healing by enhancing fibroblast proliferation and migration.